Multi-Stage Magma Evolution in Intra-Plate Volcanoes: Insights From Combined in situ Li and Mg–Fe Chemical and Isotopic Diffusion Profiles in Olivine - Steinmann, Lena K.; Oeser, Martin; Horn, Ingo; Weyer, Stefan (Frontiers in Earth Science, 2020)
Understanding the timescales of magma evolution and ascent is essential for interpreting geophysical monitoring signals from active volcanoes. In this study, we explore the potential of diffusion-driven Li concentration and isotope zoning profiles recorded by magmatic olivine crystals to unravel time scales of magma evolution processes. Lithium is a fast-diffusing element and may provide the opportunity to investigate changes in magma composition during magma ascent, shortly before eruption. Lithium chemical and isotopic profiles were determined in olivines from two localities in the Massif Central volcanic region (France) that have previously been investigated for their Fe–Mg isotope systematics. The combined investigation of isotopic and chemical profiles makes it possible to distinguish between crystal growth and diffusion events. Extremely low δ7Li-values down to −30.7‰ (relative to the commonly used Li isotope standard IRMM-16) in the crystal core regions and elevated values at crystal rims (δ7Li ∼8 to 10‰), along with increasing concentrations from cores (∼3 to 1 μg/g) toward rims (12 to 6 μg/g) were found. The shape and orientation of both the chemical and isotopic profiles indicate that they were dominantly generated by Li diffusion into and within the olivine grains during magmatic differentiation. While Mg–Fe isotope and major element profiles have been modeled by a single diffusion event (Oeser et al., 2015), concentration and isotope profiles of Li indicate that a second diffusion event took place, that was not recorded by the Mg–Fe exchange diffusion couple. The first diffusion event was interpreted as reflecting the residence of the olivine crystals in a magma chamber. As diffusion coefficients for Fe–Mg exchange diffusion are very well determined, the time scales of this event are likely best quantified by Mg–Fe isotopic exchange diffusion modeling (Oeser et al., 2015). This event probably also generated the low δ7Li observed in olivine cores. Comparing the length of the Mg–Fe and Li profiles could thus be used to determine the less well-known diffusion coefficients of Li in the studied olivine crystals. The findings of this study indicate that Li diffusion at low Li concentration levels, as typically observed in natural olivine, may be not as fast as previously thought. The second diffusion event might represent a short-lived event, such as degassing, related to the ascent of the magma and/or magma cooling after emplacement of the lava. Such a process would only affect Li, which, in contrast to the refractory elements Fe and Mg, is volatile during degassing. The findings of this study show that, according to their different diffusion rates and physiochemical properties, the combined use of spatially resolved Li and Mg–Fe chemical and isotopic diffusion profiles, is a powerful tool to model even multi-stage evolution processes in magmatic systems.